Recovery of 157 COVID-19 patients with tailored treatment regime: a single centre study at dedicated COVID hospital in India - Samant, Prafulla; Godse, Ajay; Gautam, Swapnil; Sankhe, Ajay; Gourabathini, Sivaprasad; Karpe, Rishikesh; Gawali, VijayKumar; Ali, Heena; Bagul, Mayur (International Journal Of Community Medicine And Public Health, 2020)
Background: The regimen in treatment of COVID-19 disease patients is quite variable, with wide range of outcomes. We present our successful recovery rates of COVID-19 disease patients with our tailored treatment based on comorbidity and clinical symptoms. Methods: We retrospectively analysed 157 consecutive discharged patients with COVID‐19 from 20th March 2020 to 20th May 2020. They were admitted and treated at Pandit Bhimsen Joshi general hospital. Results: The Gender distribution was 86 (54.8 %) males and 71 (45.2%) females. Mean length of hospital stay was 13 days. Among the total of 157 patients, 41(26.1%) had co-morbidities. Study results revealed that patients with comorbidities have three times (OR=2.92) higher risk of death compared with patients without any comorbidities. Diabetic patients have four times (OR=4.1) higher risk of death compared with patients without any comorbidities. X-ray of patients showed 88% had no pulmonary involvement, 6.3% bilateral alveolar shadow, 3.18% unilateral alveolar shadow and 2.54% unilateral consolidation. Conclusions: Generally, focus is on fever as primary symptom, our majority patients were asymptomatic. Three tailor made regimens approach for asymptomatic, mild cases and moderate to severe COVID-19 cases yielded in good recovery rate. Study results revealed that patients with comorbidities have three times (OR=2.92) higher risk of death compared with patients without any comorbidities. Diabetic patients have four times (OR=4.1) higher risk of death compared with patients without any comorbidities.